PERBANDINGAN HASIL KAJIAN EKSPERIMENTAL KUAT TARIK TULANGAN SIRIP DAN POLOS MENGGUNAKAN CHEMICAL EPOXY ADHESIVE BETON ITEWE - Darnianti, Darnianti; Tarigan, Ronald Rezeki; Laia, Fiber Jean Smara; Vernando W, Jeremi Liliteo (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2023)
Reinforcement strength experimental studies were carried out to determine the quality of the concrete being worked. The positive impact on every construction project in all parts of the world, the real proof of it all is with the establishment of skyscrapers, the longest bridges and various amazing things. The design of the test object used in this study is the design of the existing concrete and the design of the location of the reinforcement. The test was carried out on the quality of concrete by using a hammer test. Hammer Test is used to obtain supporting values from testing the quality of the concrete. This research examines the adhesive power of chemical epoxy adhesive concrete because this chemical epoxy adhesive concret e has become one of the solutions in reinforced concrete problems, where the function of this chemical epoxy adhesive concrete is to bond reinforcing steel to existing concrete, in the research that will be carried out by the author using chemical epoxy adhesive concrete with the product brand Itewe Neo1 which varies with the diameter of steel fin reinforcement D10, D13 and D16, the purpose of this study was to determine the specifications and the effect of the adhesion of chemical epoxy adhesive concrete Itewe Neo1 to steel fin and plain steel.